A study on adjustable height stand for temperature scanner - Mohammad Shahrul Nizam, Amin Nuddin; Norazlianie, Sazali; Ahmad Shahir, Jamaludin; K., Kadirgama; D., Ramasamy; Wan Sharuzi, Wan Harun (Semarak Ilmu Publishing, 2023)
This research project aimed to transform a common temperature scanner stand into a user-friendly adjustable stand holder temperature scanner. The temperature scanner automatically adjusts its height according to the user's height, reducing the risk of contact infection by using an ultrasonic sensor to detect the user in front of the scanner. The experiment involved measuring the time taken for the thermometer to move from the starting position to the maximum height of different individuals with varying heights. A frame capture application on a smartphone was used to record the motion and time, capturing data at a rate of 33 frames per second for accuracy. The tests were conducted using a constant motor speed of 100 revolutions per minute. The results showed that the duration of waiting time for the adjustable stand holder temperature scanner was valid for individuals with heights ranging from 100 cm to 180 cm. The constructed adjustable stand successfully served its purpose and demonstrated functionality and reliability in real-life testing. To improve the accuracy and expand the capabilities of the adjustable stand holder temperature scanner, future work are needed such as utilizing smart system programs to cater to user preferences, implementing material modifications to reduce vibrations, and introducing additional features to indicate a person's height and weight.